On thermal stability of antimony thin films for solar cells applications - Shongalova, A.; Muratov, D.; Rakhmetov, B.; Aimaganbetov, K.; Zhantuarov, S. (Recent Contributions to Physics, 2019)
Antimony has received considerable attention due to structural archetype for a variety of sulfide and sulfosalt minerals. In this work Sb thin films with thickness of 300 - 400 nm were grown by radio frequency magnetron sputtering, in order to use as a precursor to synthesize chalcogenide semiconductors for solar cells applications. It was shown the influence of annealing temperatures to the structure of the as-deposited Sb films. Antimony thin films were deposited on a glass substrate and subsequently were annealed at different temperatures 300°C, 400°C, 500°C in argon gas ambient. Structural characterization of the films analyzed by Raman scattering spectroscopy, two different excitation wavelengths were used: 532, 632.8 nm. Raman bands both the symmetric (A1g) and nonsymmetrical (Eg) phonons were identified. Transmittance measurements and morphology studies of the films showed stability of annealed films at temperatures at 400 °C and the results of Raman spectroscopy showed their high polycrystalline structure.